Profile of Multi Drug Resistant Tuberculosis (MDR-TB) Patients Using Anti-TB Drugs in the Outpatient Unit of RSUD Poso Year 2022 - Ajeng Kurniati Roddu; Suherman Baharuddin; Nur Aini Amir (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study was to determine and further examine the description of Multi Drug Resistant Tuberculosis (MDR-TB) patients who have used anti-tuberculosis drugs in the Poso Regional General Hospital outpatient unit. This type of research is a non-experimental descriptive study (retrospective in nature) using research instruments in the form of data collection (prescriptions or medical records) of outpatient MDR-TB patients at the Poso Regional General Hospital, Central Sulawesi in 2022. Based on the results of research that has been conducted in the period January - December 2022, it can be concluded that the characteristics of treatment in Tuberculosis patients as a whole are 226 people, there are patients with MDR-TB drugs 16 people (7.08%), with a total of 127 prescription sheets (11.28%), the potential for drug interactions 36 prescriptions (28.35%) and no interactions 91 prescriptions (71.65%). Types of opportunistic infections are with a history of diabetes mellitus (DM) 6 people (37.50%), comorbid kidney and liver disease 2 people (12.50%), HIV-AIDS disease 2 people (12.50%), pneumonia 5 people (31.25%), fungal infection 1 person (6.25%). The average use of MDR-TB drugs with more than 1 type of drug will produce drug side effects on initial therapy and continued therapy with a total of 14 cases (87.50%) with different drug side effects and 2 people (12.50%) who did not experience drug side effects